Grape pomace supplementation reduced methane emissions and improved milk quality in lactating dairy cows - A. Akter; X. Li; E. Grey; S.C. Wang; E. Kebreab (Journal of Dairy Science)
ABSTRACT: Grape pomace (GP) is a byproduct of the viticulture industry and shows promise for feeding dairy cattle as well as reducing enteric methane (CH4) emissions. This study investigates the potential of using fresh GP in dairy cow feeding and its effects on CH4 emissions. Multiparous Holstein dairy cows (n = 24, 205 ± 39 DIM) were housed in freestall barns and provided rations consisting of alfalfa hay, wheat hay, almond hulls, cottonseed, and grain mix. After a 2-wk adaptation period, cows were randomly assigned to one of the 3 treatments: a control diet (CON), a diet with 10% grape pomace (10% GP), and a diet with 15% GP (15% GP) on a DM basis. Treatments were arranged in a 3 × 3 Latin square design, where cows received 3 treatments over 3 periods, each period lasting for 4 wk. Rations were provided twice daily and gas emissions from cows were measured using an automated GreenFeed system. Milk production was recorded both in the morning and evening, and milk samples were collected weekly for fat, protein, lactose, SNF, MUN, and SCC analysis. For fatty acids analysis, milk samples were collected on the last 3 d of each 28-d period. Data were checked for normality and were analyzed using a mixed model ANOVA in proc GLIMMIX in SAS. Dry matter intake was reduced in GP-fed cows, where CON had the highest DMI followed by 10% and 15% GP. Methane and H2 emissions were reduced in GP-supplemented group compared with CON group. On the other hand, CO2 emissions was found higher in the GP-supplemented groups compared with the CON group. Milk yield was not different among different GP treatments. Although no differences were observed in fat, protein, lactose, SNF, and SCC, we did observe that MUN was lower in the 10% and 15% GP groups compared with the CON group. The reduction in CH4 emissions in the GP-supplemented groups suggests that the chemical components of GP were effective in reducing CH4 emissions. In contrast, the lower DMI in GP-supplemented groups indicates that DMI can act as an indicator of lower CH4 production. No effects on fat, protein percentage, and milk yield indicated that GP did not negatively affect milk production. Total PUFA and linoleic acid in milk fat were greater in 10% and 15% GP groups compared with the CON group. In conclusion, GP supplementation helped reduce enteric CH4 emissions from cows without affecting milk production.